الراوي العين في كتاب بلاغات النساء لابن طيفور - سعيد السريحي الحربي, صلوح مصلح (Revues faculté des lettres et des langues; No 17 (2015): مجلة كلية الآداب واللغات)
يعد الراوي عتبة من عتبات النص، وعنصراً هاماً من عناصر البناء السردي؛ فهو الصانع له، والمتحكم في بناء العلاقات بين مكوناته والوسيط بين المادة المروية والمتلقي. يثير بتصدره النص السردي العديد من التساؤلات حول: العين التي رأت المشهد السردي. الصوت الذي نقل هذه الرؤية. الزمن الذي تمت فيه الرؤية. دور الراوي في البناء السردي. وتبعاً لهذه التساؤلات ستقف الدراسة على الراوي بوصفه العين التي ترى المشاهد السردية ثم تعيد صياغتها لتجعل من المتلقي شريكاً في الرواية. تتخذ الدراسة من كتاب بلاغات النساء لابن طيفور مادة لها ومن المنهج الوصفي المستعين بآلية التحليل أداة للولوج إلى عالم السرديات  Narralology ومحاولة الإفادة من الرصيد النظري والإجرائي والاصطلاحي للسرديات الحديثة مع الوفاء للنص باعتباره ممارسة لغوية متميزة. ستقف الدراسة على مفهوم الراوي العين وعلاقته بالمروي ، وتربط بين الرؤية البصرية والوصف ،وتكشف عن العلاقة بين الوصف والسرد ،للوصول إلى أنماط الراوي العين وتحديد الرؤية وطريقة الرواية عند كل منهم ودورهم في البناء السردي . تهدف الدراسة إلى الإسهام في إعادة قراءة تراثنا النثري بصفة عامة، والوصفي بصفة خاصة كما تسعى إلى الكشف عن أنماط الراوي العين في كتاب بلاغات النساء لابن طيفور ودوره في البناء السردي . The narrator is one of the most significant narrative elements. The narrator constructs and directs elements in the narrative. The narrator is a mediator between the narrative and the recipient. Such a major role brings to light several questions regarding the eye-witness character that observes the scene of actual incident, the voice that transfers the description of the scene, the span of time for narration as well as the function of the narrator in the narrative structure.             The aim of this research is to propose answers for those above issues where the eye-witness narrator is concerned especially when the narrator firstly reformulates the incidents witnessed, and secondly involves the recipient to take part in the process of re-narration .              Methodology in this study relies on descriptive and analytical approaches of the writing style in Ibn Tayfur’s   Balaghat al-Nisa. This study aims to contribute to the field of   Narratology  by undertaking to review the literature  and terminology in modern narratology.  Giving due attention to the notion of writing  in Ibn Tayfur constitutes the core of this paper.              The paper will also investigate the relationship between the narrated and the narrator,  the visual and the descriptive, and the visual and the narrative. By doing so, the study explores the types of the eye-witness narrator and their means in illuminating the visual and their techniques along with their structures in narration.             This paper contends  to reread the Arabic heritage in prose, in general, and the descriptive narrative through Ibn Tayfur’s   Balaghat al-Nisa in particular. Key words: Narration, eye-witness narrator, rereading, reformulating, descriptive heritage.